2001
DOI: 10.1130/0016-7606(2001)113<0482:geoeat>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Geologic evidence of earthquakes at the Snohomish delta, Washington, in the past 1200 yr

Abstract: Exposed channel banks along distributaries of the lower Snohomish delta in the Puget Lowland of Washington reveal evidence of at least three episodes of liquefaction, at least one event of abrupt subsidence, and at least one tsunami since ca. A.D. 800. The 45 measured stratigraphic sections consist mostly of 2-4 m of olivegray, intertidal mud containing abundant marsh plant rhizomes. The most distinctive stratigraphic unit is a couplet comprising a 0.5؊3-cm-thick, laminated, fining-upward, tsunami-laid sand be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 33 publications
1
57
0
Order By: Relevance
“…Evidence of fault motion could be expressed in the geomorphology, surface sediments and shallow stratigraphy of this environment as follows: 1) geomorphologic change that includes formation of open water areas and expansion of water bodies into unique geometries within the marsh interior (White and Morton, 1997;Gagliano et al, 2003;Nichol et al, 2007); 2) quantifiable changes or patterns in fluvial geomorphology, including variations of river and distributary planforms, channel sinuosity, and gradients (Burnett and Schumm, 1983;Maroukian et al, 2008); 3) localized and accelerated wetland loss and rates of subsidence (Morton et al, 2002;Shinkle and Dokka, 2004); 4) quantifiable lateral discontinuities near fault surface traces in sediment accumulation rates over small spatial scales; and 5) subsurface indicators including lateral chronostratigraphic offsets of dated facies, and/or lithostratigraphic or biostratigraphic offsets of facies or fossil assemblages over short distances (400 m), and/or high-resolution seismic reflectors that display deformation in the form of offsets, unique terminations, and abrupt changes of reflector orientations and trends (e.g., Bourgeois and Johnson, 2001;Hayward et al, 2004;Ferranti et al, 2008;Nixon et al, 2009). Other studies focused on the geomorphology and stratigraphy of coastal Louisiana have noted similar physical relationships with fault motion (e.g., Holbrook and Schumm, 1999;Dokka et al, 2006;Morton et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of fault motion could be expressed in the geomorphology, surface sediments and shallow stratigraphy of this environment as follows: 1) geomorphologic change that includes formation of open water areas and expansion of water bodies into unique geometries within the marsh interior (White and Morton, 1997;Gagliano et al, 2003;Nichol et al, 2007); 2) quantifiable changes or patterns in fluvial geomorphology, including variations of river and distributary planforms, channel sinuosity, and gradients (Burnett and Schumm, 1983;Maroukian et al, 2008); 3) localized and accelerated wetland loss and rates of subsidence (Morton et al, 2002;Shinkle and Dokka, 2004); 4) quantifiable lateral discontinuities near fault surface traces in sediment accumulation rates over small spatial scales; and 5) subsurface indicators including lateral chronostratigraphic offsets of dated facies, and/or lithostratigraphic or biostratigraphic offsets of facies or fossil assemblages over short distances (400 m), and/or high-resolution seismic reflectors that display deformation in the form of offsets, unique terminations, and abrupt changes of reflector orientations and trends (e.g., Bourgeois and Johnson, 2001;Hayward et al, 2004;Ferranti et al, 2008;Nixon et al, 2009). Other studies focused on the geomorphology and stratigraphy of coastal Louisiana have noted similar physical relationships with fault motion (e.g., Holbrook and Schumm, 1999;Dokka et al, 2006;Morton et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…11). Strong ground motion associated with the most recent earthquake on the Utsalady Point fault may have also caused liquefaction dated to about A.D. 1430 to 1640 in the Snohomish River delta (Bourgeois and Johnson, 2001) (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Paleoseismologic studies have shown that at least five to seven Holocene ground-rupturing earthquakes have occurred (Bucknam et al, 1992;Sherrod et al, 2000;Nelson et al, 2003;Kelsey et al, 2004). Evidence exists that show that earthquake associated deformation of the seafloor or associated landslides have produced tsunamis (Atwater and Moore, 1992;Bourgeois and Johnson, 2001;Williams and Hutchinson, 2000;Williams et al, 2005), which have a potential of impacting the habitats within Admiralty Inlet. Multibeam echosounder bathymetric image with interpreted potential benthic habitat types in the vicinity of the originally-proposed Snohomish tidal turbine sites offshore Admiralty Head, Whidbey Island, Washington.…”
Section: Seismicitymentioning
confidence: 94%